Pengaruh Palm Oil Mill Effluent (Pome) Pada Proses Pengomposan Tandan Kosong Sawit Sisa Media Jamur Merang (Volvariella Volvacea) - Muhamad Ghifar Alharis; Elvi Yenie; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The empty fruit bunch (EFB) is a solid waste produced in large quantities byindustrial processing of palm oil through 23% of fresh fruit bunches (FFB). EFB is a waste of lignocellulose containing lignin, hemicellulose, and cellulose. The high lignin content in the EFB affects the length of decomposition period. It can be accelerated by adding of white mushrooms, one of paddy straw mushroom (Volvariella volvacea). This research aims to examine the effects of paddy straw mushroom in degrading lignin, C/N, and the effect of adding POME with residual EFB of the mushroom media to the C/N ratio, content of N, P, and K. The method used within two variations of planting mushrooms is precisely by mixingand spreading. The best planting is by implementing the mixed variation with the degradation results of lignin toward EFB of 10.582% and the value of C/N ratio of 38.8. The composting process used in-vessel system and the effect of variation in adding 1 kg of POME, 1.5 kg of POME, and 2 kg of POME to EFB. The greatest value of C/N ratio in adding 2 kg of POME equal to 15.13%. Nitrogen content (N) of 2.64 %, Phosphorus (P) equal to 1.10 %, and Potassium (K) equal to 1.10 % is in accordance with the standard of compost quality of Indonesian Standard National 19-7030-2004.Keywords : Empty fruit bunches, paddy straw mushroom, lignin degradation, POME, invessel system , composting